The Influence of Corporate Social Responsibility and Profitability on Tax Avoidance - Nirsetyo Wahdi; Widji Astuti; Prihat Assih (Innovation Business Management and Accounting Journal, 2024)
The urgency of the research is that there is new research on the factors influencing tax avoidance. Based on the literature or journal reference collection, this research has novelty compared to previous research, namely adding independent variables, changing the company object, and updating the research year. The type of research used is quantitative research. The population in the study were all manufacturing companies on the Indonesian Stock Exchange in 2017-2021. Data collection is a step-by-step process for compiling data according to the character and needs of the research. The data collection technique in this research is the documentation method. Documentation is done by reading and taking notes from books, research journals and internet downloads. This research will test the moderating effect of audit quality on the relationship between corporate social responsibility, profitability and tax avoidance variables. This method is completed using Moderated Regression Analysis (MRA). This research shows that the first regression model shows no significant influence between corporate social responsibility and partial tax avoidance. The first regression model shows a significant negative influence between profitability and partial tax avoidance.